Penerapan Case Based Reasoning pada Sistem Pendukung Keputusan Penanganan Komplain Penyewa Mall (Studi Kasus : Maspion Square Mall, Surabaya) - Meivi Kartikasari; Purnomo Budi Santoso; Erni Yudaningtyas (Fakultas Teknik, Universitas Brawijaya, 2015)
Abstract-One of the factors affecting the level of satisfaction of tenants in a mall is the speed and accuracy of the services provided by the manager of the mall, especially in terms of the handling of complaints. Case Based Reasoning is a method to resolve the issues with respect to the same events in the past, then use the knowledge or information to solve new problems. This research aims to develop a Decision Support System with Case Based Reasoning method to improve complaint handling services to tenants mall. Results of this research is a prototype complaint management system called SIPENKOM that can generate output solutions for new cases based on similar old cases. Based on test to tenants and management of Maspion Square Mall, SIPENKOM can improve complaint handling services by approximately 85%. Keywords-Decision Support Systems, Case Based Reasoning, Similarity.